(untitled) (Herald of Journalism, 2018)
The material contained in the book by American writer and journalist George Kennan’s «Siberia and the Exile System», has greatly expanded information about the life of political exiles. Kennan’s book, caused deep dissatisfaction with the ruling circles of Russia and got a worldwide repercussions. The main value for modern historical science and the history of journalism represents information about the life of Kazakhs collected by a foreign author. The analysis of the material showed that everything connected with the life, present and future of the Kazakh people, illuminated, considered, evaluated from the point of view of socio-economic development of Russia.